2018
DOI: 10.1016/j.nicl.2018.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal functional corticomuscular coupling after stroke

Abstract: Motor dysfunction is a major consequence after stroke and it is generally believed that the loss of motor ability is caused by the impairments in neural network that controls movement. To explore the abnormal mechanisms how the brain controls shoulder abduction and elbow flexion in “flexion synergy” following stroke, we used the functional corticomuscular coupling (FCMC) between the brain and the muscles as a tool to identify the temporal evolution of corticomuscular interaction between the synkinetic and sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 61 publications
2
36
0
Order By: Relevance
“…Furthermore, compared with the controls, the bidirectional total and nonlinear information flows in both the beta and gamma bands of the stroke group were significantly reduced. This result was consistent with the previous studies [ 5 , 51 53 ]. This weakening of FCMC may be caused by cortical damage or muscle changes resulting from stroke [ 5 , 54 ].…”
Section: Discussionsupporting
confidence: 94%
“…Furthermore, compared with the controls, the bidirectional total and nonlinear information flows in both the beta and gamma bands of the stroke group were significantly reduced. This result was consistent with the previous studies [ 5 , 51 53 ]. This weakening of FCMC may be caused by cortical damage or muscle changes resulting from stroke [ 5 , 54 ].…”
Section: Discussionsupporting
confidence: 94%
“…Furthermore, subjects who were pregnant, had been previously diagnosed with severe dysphasia or hypertension, or participated in any intensive upper limb physical practice or botulinum toxin treatment within 1 year before the current experiment were excluded from participating in the research. According to the previous studies (26,33,34), the gender factor did not significantly affect the CMCoh parameters. Hence, we had no specific requirement on the gender in the recruitment process.…”
Section: Subject Recruitmentmentioning
confidence: 69%
“…In the current study, we found significant peak CMCoh (CMCoh (σ ) > 0.0170) of all UE muscles in chronic stroke patients during both 20 and 40% Fx schemes. This suggested that the corticomuscular coupling has been reestablished during the chronic stage of stroke (19,26). However, the reconstructed pattern could be different from that of the CMCohs observed among the movements of the unimpaired subjects.…”
Section: Finger Flexionmentioning
confidence: 88%
See 1 more Smart Citation
“…The only apparent differences between both data acquisition methods were the improved sound quality and the loss of need to strap sensors to patient limbs. In order to further elucidate the neurophysiological underpinnings of musical sonification therapy we simultaneously recorded EEG and EMG data from a subset of patients to analyze corticomuscular phase coherence during upper limb movements (Chen et al, 2018;Pan et al, 2018). According to previous studies (Pan et al, 2018) we hypothesized that cortico-muscular phase coherence increases in the ipsilesional hemisphere after musical sonification therapy.…”
Section: Introductionmentioning
confidence: 99%